2011
DOI: 10.1007/s12098-011-0405-1
|View full text |Cite
|
Sign up to set email alerts
|

Normal Oxygen Saturation Trend in Healthy Term Newborns within 30 Minutes of Birth

Abstract: The study defines the normal SpO(2) in healthy term newborns of NVD and CS delivered newborns and also concludes that there is no significant difference in SpO(2) among NVD and CS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
0
8
1
Order By: Relevance
“…The finding of preterm babies taking relatively longer duration than term babies for first detection of saturation as also been documented earlier [3][4][5]. Similarly, longer time taken for measurement in babies delivered by caesarean section has also been documented [6].The limitation of our study was presence of dedicated personnel for probe attachment and data recording, which may not be feasible in practical situations, and which can further prolong the time taken for measurement in actual settings.This observational study assessed the feasibility of using pulse oximeter during neonatal resuscitation in 428 term and preterm (32-36 weeks) neonates. The oxygen saturation reading was obtained by 1-minute in 152 (35.5%) neonates.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…The finding of preterm babies taking relatively longer duration than term babies for first detection of saturation as also been documented earlier [3][4][5]. Similarly, longer time taken for measurement in babies delivered by caesarean section has also been documented [6].The limitation of our study was presence of dedicated personnel for probe attachment and data recording, which may not be feasible in practical situations, and which can further prolong the time taken for measurement in actual settings.This observational study assessed the feasibility of using pulse oximeter during neonatal resuscitation in 428 term and preterm (32-36 weeks) neonates. The oxygen saturation reading was obtained by 1-minute in 152 (35.5%) neonates.…”
mentioning
confidence: 53%
“…The finding of preterm babies taking relatively longer duration than term babies for first detection of saturation as also been documented earlier [3][4][5]. Similarly, longer time taken for measurement in babies delivered by caesarean section has also been documented [6].…”
mentioning
confidence: 64%
“…[25][26][27][28][29] It has been reported that peripheral capillary oxygen saturations take up to 15 minutes to stabilise, 25 heart rate up to one hour 6 and, up to three days for functional closure of the four circulatory ducts. 1,3 However, there is paucity in data for the remaining transition period, which takes approximately 12-72 hours.…”
Section: Discussionmentioning
confidence: 99%
“…12 On the other hand, there are also some studies which support the fact that the mode of delivery does not affect the SpO 2 progression. 13,14 The present study was conducted with a new generation pulse oximeter with a neonatal probe keeping in mind the guidelines provided by the American Academy of Paediatrics to reduce the motion artefacts and other pitfalls. All the readings of colour and SpO 2 were taken by a single observer to minimize inter-observer variations.…”
Section: Discussionmentioning
confidence: 99%